Neil Hopkinson, A Helenistic Anthology, Cambridge University Press, Cambridge Greek and Latin Classics, 1988, 288 pp. ISBN 0-521-31425-9 (Minerva, 2019)
Review: Neil Hopkinson, A Helenistic Anthology, Cambridge University Press, Cambridge Greek and Latin Classics, 1988, 288 pp. ISBN 0-521-31425-9